She who is ... Invisible?: A Glimpse of the Mothering God in the Church of England's Eucharistic Prayers - Brooks, Bess ca. 20./21. Jh. (Journal of the European Society of Women in Theological Research, 2020)
This article contends that, when we think of regimes of (in)visibility, we should begin with God and, specifically, how we describe God in public worship. The essay highlights the invisibility of female aspects of God in the current Church of England (CofE) Eucharistic Prayers. There is a single reference to God as mother in Prayer G and the author argues that the inclusion of this reference is characterised by defeminisation: that is, the masculine aspect of something dominates to the extent that the female aspect cannot manifest. The author suggests that defeminisation occurs at three levels: in the historic dominance of the Father metaphor as a way of describing God, in the lack of value placed on feminist scholarship in the CofE General Synod debates about Prayer G, and in the inadequacy of the mother reference itself. The mother God, as depicted in Prayer G, does not feed her children, unlike the father God in Prayers B, E, and F. The author suggests that future revisions of CofE Eucharistic Prayers should increase the visibility of female aspects of God. The article is set within the overall context of Gail Ramshaw’s hermeneutical approach to liturgy, YES-NO-YES, and her concept of liturgy as primary speech.